Interaction between competition law and corporate governance : opening the 'black box' - Thépot, Florence (Global competition law and economics policy, 2019)
"Competition law and corporate governance: two distinct orders Antitrust is about markets; corporate [governance] is about firms. Antitrust is about competition; corporate [governance] is about cooperation. Antitrust regulates relations among firms; corporate [governance] governs relations within firms. Operating in distinct conceptual orders - that of the marketplace and that of the firm- competition law and corporate governance pursue different objectives. Competition law is oriented towards the defence of consumers' interests in the market while corporate governance rules are designed to protect the interests of shareholders. Competition law and corporate governance also constitute separate areas of academic inquiry across jurisdictions. The aim of this book is to fill a gap in the scholarship, by establishing systematic connections between competition law and corporate governance, regarding both substantive and enforcement issues of contemporary relevance"--